EFFECT OF HEAT STRESS ON IN VITRO POLLEN DEVELOPMENT IN FRUIT TREES - Gur, Nazmi; Yolacti, Semiha; Topdemir, Aykut (Parlar Scientific Publications (P S P), 2019)
We investigated the effect of temperature, an important stress factor for plants, on pollen germination and pollen tube length in vitro in three species of fruit tree, apricot (Prunus armenica L.), plum (Prunus domestica L.) and quince (Cydonia oblanga Miller). All samples were collected as far away from environmental pollution as possible. Pollen was incubated at temperatures between 5 and 35 degrees C (controls at 22 +/- 1 degrees C) on Brewbaker and Kwack medium for 3 h. The pollen of each species was affected differently depending on incubation temperature. At low temperature, pollen germination in apricot was affected most, and at high temperature, plum was most affected. At low temperature, pollen tube elongation was most affected in quince, whereas at high temperature, apricot was most affected.
Keywords: In vitro; pollen germination; pollen tube growth; heat stress